Letter: role of mean platelet volume levels in the prediction of major acute cardiovascular events in patients with non‐alcoholic fatty liver disease—authors' reply. Issue 10 (28th October 2019) - Mullish, Benjamin H.; Forlano, Roberta; Abeles, R. Daniel; Thursz, Mark R.; Manousou, Pinelopi
Abstract : LINKED CONTENT This article is linked to Abeles et al and Liu et al papers. To view these articles, visit https://doi.org/10.1111/apt.15192 and https://doi.org/10.1111/apt.15527 .